Pemberontakan Kaum Muda terhadap Adat Minang dalam Novel Memang Jodoh Karya Marah Roesli: Penelitian Sosiologi Sastra - Sri Wahyuningsih (Universitas Muhammadiyah Prof. DR. HAMKA, 2016)
This study aimed to obtain information about the resistance or rebellion against indigenous youth Minang culture contained in the novel Memang Jodoh by Marah Roesli by using a sociological approach to literature. The method used in this research is descriptive qualitative method, with analysis of objects such as text in a novel based on the structure and extrinsic elements in the cultural aspect with the approach of sociology of literature. The results obtained from this research that addresses the issue sociology of literature and resistance to traditional Minang. In the analysis of sociology of literature identified in the system of culture, politics, ethics, religion, economics, and education. In the novel dating Indeed, sociologically, in Padang matrilineal society that is organized according to the structure of the maternal line. Therefore, every mother feels has the power to his son than his father. Customs in Padang, Padang tall nobleman should not marry someone from outside Padang because it is considered as a major humiliation in the eyes of Padang, especially over a women. Padang custom are binding should not be denied by society. If denied, the penalty for them is removed from the family and is no longer considered ethnic Padang. Furthermore, the results of the analysis of resistance to traditional Minang, Hamli as the main character in the novel is a figure of the young people who are forced to deal with customs attached. Resistance against indigenous young people can be in two forms, both physical and non-physical. Physically, as did Hamli, the resistance can be done by leaving the homeland for reasons uncomfortable someone about a problem customs. Furthermore, in non-physical to do with the debate, a rejection of the decision deliberation traditional leaders / family, and you can also academic education as high as possible in order to have more science to improve an outdated custom. At least those of them that are carried out by Hamli in the face of custom in his family.